REPRESENTASI WACANA BERITA PILPRES DI MEDSOS - Reka Yuda Mahardika; Yusep Ahmadi F (STKIP Siliwangi, 2020)
The background of this research is the large number of tendentious reports that are pro or contra against presidential candidate pairs. The purpose of this research is to represent procontra and tendentious news which is spread on social media. The method used is the descriptive method with analytical knife used to elaborate the news text is the van dijk type critical discourse analysis (AWK). Using van Dijk 's analysis knife, it was found that the news on that were distributed on social media did not objektif ethical principles and were tendentious towards presidential candidate pairs